2014
DOI: 10.1063/1.4896488
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature near band edge recombination dynamics in ZnO nanorods

Abstract: Articles you may be interested inThe surface-plasmon-resonance and band bending effects on the photoluminescence enhancement of Agdecorated ZnO nanorods J. Appl. Phys. 116, 063108 (2014) The recombination dynamics of neutral donor bound excitons (D o X: I 4 , I 6/6a ) and near band edge defect-related emission in solution grown ZnO nanorods are investigated using steady state and time-resolved photoluminescence (PL) measurements. The effects of annealing are also studied. Low temperature steady state PL shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 41 publications
0
25
0
2
Order By: Relevance
“…The most detail study of this transition was reported by Yalishev et al [12] and Wagner et al [3]. In their work, the 3.33 eV emission line was attributed to recombination of excitons bound to extended structural donor defect complexes which disappear at temperature of 10 K. Study done by Urgessa et al [26] on ZnO nanorods growth for temperature dependent PL also observe dominance of donor-bound exciton as possible reason for this emission. Fig.…”
Section: Temperature Dependent Plmentioning
confidence: 82%
See 1 more Smart Citation
“…The most detail study of this transition was reported by Yalishev et al [12] and Wagner et al [3]. In their work, the 3.33 eV emission line was attributed to recombination of excitons bound to extended structural donor defect complexes which disappear at temperature of 10 K. Study done by Urgessa et al [26] on ZnO nanorods growth for temperature dependent PL also observe dominance of donor-bound exciton as possible reason for this emission. Fig.…”
Section: Temperature Dependent Plmentioning
confidence: 82%
“…Band edge emission centered at around 398.3 nm should be attributed to the recombination of excitons and V Zn [24,25]. However the origin of violet emissions centered at 3.07 eV(402.79 nm), 406.9 nm (3.04 eV) and 409.6 nm (3.02 eV) are ascribed to an electron transition from a shallow donor level of neutral Zn i to the top level of the valence band [26,27,9]. The broad deep level emission that started from UV to the visible region 360-480 nm with the maximum peak at 409.64 nm for the sample prepared at°200 C was observed.…”
Section: Structural Analysismentioning
confidence: 97%
“…Additionally, the symmetry in the I-V curve (around 0 V) suggests that the nanorods are also heavily doped. It is also instructive to note that hydrogen, always present in these ZnO nanostructures, has been identified as a shallow donor and is most likely responsible for the large free carrier concentration at room temperature [13]. The I-V characteristics of heterojunction B, however, displays substantial rectification with a rectification ratio of 19 measured at 0.5 V ± .…”
Section: Resultsmentioning
confidence: 99%
“…Немонотонное поведение интенсивности полосы NBE при термическом отжиге на воздухе с максимумом при ∼ 300−400 • С наблюдалось в ряде работ и объяснялось увеличением степени кристал-личности [11], десорбцией с поверхности гидроксильных групп [12] и примесных атомов, вызывающих безызлуча-тельную рекомбинацию [13].…”
Section: экспериментальные результатыunclassified
“…Пред-полагается, что межузельный водород нестабилен при комнатной температуре и отжигается за несколько недель [28], а водород в позиции замещения стабилен до ∼ 500 • С [29,30]. В спектрах низкотемпературной ФЛ мелкому водородному донору, вводимому Н-обработкой, приписывают полосу I 4 [13,31,32] при ∼ 3.363 эВ, ко-торая идентифицирована как водород в кислородной вакансии (H O ) [33]. Водородному донору приписывают также линию при 3.360 эВ, идентифицированную как мелкий донор -водород в BC положении [33].…”
Section: обсуждение результатовunclassified